Soil properties, crop productivity and energetics under different tillage practices in fodder sorghum + cowpea – wheat cropping system. Issue 4 (21st March 2019) - Dixit, Anoop Kumar; Agrawal, Rajiv Kumar; Das, Sanjoy Kumar; Sahay, Chandra Shekhar; Choudhary, Mukesh; Rai, Arvind Kumar; Kumar, Sunil; Kantwa, Sita Ram; Palsaniya, Dana Ram
ABSTRACT: Tillage is an important agricultural operation which influences soil properties, crop yield and environment. Nine combinations of three tillage practices including conventional tillage (CT), minimum tillage (MT) and zero tillage (ZT) were evaluated in fodder sorghum ( Sorghum bicolor ) + cowpea ( Vigna unguiculata ) – wheat ( Triticum durum ) cropping system for 5 years (2009–2014) on clay loam soil under limited irrigation. Continuous ZT practices significantly improved surface soil organic carbon, bulk density, infiltration rate and maximum water holding capacity. Carbon sequestration rate, soil organic carbon stock and soil enzymatic activities were relatively more under ZT than CT-CT practice. Higher fodder yield of sorghum + cowpea was recorded with CT ( kharif ) while wheat grain yield with ZT ( rabi ). However, the system productivity was statistically similar in all the tillage treatments on pooled data basis. The economic benefits were also maximum under ZT-ZT practice. The ZT-ZT practice recorded significantly lowest energy input (17.1 GJ ha −1 ) which resulted in highest energy use efficiency (13.6) and energy productivity (518 kg GJ −1 ). Thus, adoption of ZT significantly improved soil health, stabilized crop yield, increased profitability and energy use efficiency in the semi-arid agro-ecosystem.